Plasma ferritin concentrations are not associated with abdominal aortic aneurysm diagnosis, size or growth. (August 2016) - Moxon, Joseph V.; Jones, Rhondda E.; Norman, Paul E.; Clancy, Paula; Flicker, Leon; Almeida, Osvaldo P.; Hankey, Graeme J.; Yeap, Bu B.; Golledge, Jonathan
Abstract: Background and aims: Experimental studies using a rodent model have suggested that iron overload may contribute to abdominal aortic aneurysm (AAA) pathogenesis. Methods: We assessed the association of total body iron, as measured by plasma ferritin, with AAA diagnosis, size and growth in 4024 community-dwelling older men screened for AAA, using logistic regression and linear mixed effects models. Results: Plasma ferritin concentrations were similar in men who did (n = 293) and did not (n = 3731) have an AAA (median [inter-quartile range] concentrations 115.4 [63.0–203.1] and 128.5 [66.1–229.1] ng/mL respectively, p  = 0.124). There was no association between plasma ferritin concentration and AAA diagnosis in unadjusted logistic regression (odds ratio (OR) for a 1 standard deviation increase: 0.880 [95%CI: 0.764–1.015]; p  = 0.078), or when adjusting for AAA risk factors and factors known to influence circulating ferritin (OR for a 1 standard deviation increase: 0.898 [95% CI: 0.778–1.035]; p  = 0.138). Iron overload prevalence (plasma ferritin concentrations >200 ng/mL) was lower in men with an AAA (25.3%) than those without (30.8%; p  = 0.048), but was not associated with AAA diagnosis after adjusting as above (OR: 0.781 [95% CI:0.589–1.035]; p  = 0.086). The association of iron overload with AAA growth was investigated in 265 men with small AAAs who received at least 1 repeat ultrasound scan in the 3 years following screening. We saw no difference in AAA growth between men who did and did not have iron overload (n = 65 and 185 respectively, p  = 0.164). Conclusions: Our data suggest that iron overload is unlikely to be important in AAA pathogenesis. Highlights: There is no current medical treatment to slow abdominal aortic aneurysm (AAA) growth. Recent animal data have suggested that an iron-reduced diet protects against AAA formation, suggesting that i) total body iron overload may be involved in AAA pathogenesis. ii) reduction of iron may be a treatment for AAA. Here, we assessed whether total body iron overload as assessed by circulating ferritin concentration was associated with AAA presence, size and growth in a large cohort of community-screened men. Our data demonstrate no relationship between serum ferritin and AAA and do not support iron reduction as a therapy for AAA.